Partition Coefficients for Continuous Micellar Reaction Processes - Wille, Susanne; Mokrushina, Liudmila; Schwarze, Michael; Smirnova, Irina; Schomäcker, Reinhard; Arlt, Wolfgang (Chemical Engineering & Technology, 2011)
The micelle-water partition coefficients of reactants, products, and catalyst ligands are predicted using UNIFAC-IF and COSMO-RS. It is demonstrated that both models represent a reasonable tool for preliminary screening of the micellar systems for a specific continuous reaction process supported by micellar enhanced ultrafiltration (MEUF). The model reaction is the hydrogenation of itaconic acid and its derivatives (dialkyl esters) in the presence of a rhodium-based catalyst. The effect of the size and nature of the surfactant head group and tail is explored for nonionic and ionic surfactants. The high partition coefficients of the catalyst ligands indicate that no catalyst leakage is expected in MEUF. Based on the concentration dependence of the calculated partition coefficients, the solubilization capacity of micelles is estimated.
Keywords: Hydrogenation; Itaconic acid; Itaconic acid dialkyl esters; Micelle-water partition coefficients; Micellar enhanced ultrafiltration